PERBANDINGAN PERATURAN TENTANG MEKANISME HUKUMAN MATI MENURUT HUKUM INDONESIA DAN MESIR: Comparison of Regulations on the Death Penalty Mechanism according to Indonesian and Egyptian Law - Yunarto, Gusti Adrian; Wangga, Maria Silvya E. (AMICUS CURIAE, 2024)
The study aims to discuss the comparison of death penalty regulations in Indonesia and Egypt. Based on this, researchers use the main problem of how to regulate the death penalty according to law in Indonesia and Egypt and what are the disadvantages and advantages of the death penalty in Indonesia and Egypt. To answer these problems, normative research is carried out with the nature of analytical descriptive research and the type of data used is secondary data. In conclusion, the application of the death penalty in Indonesia is contained in the Criminal Code and other criminal laws. The implementation refers to Law No. 2 / PNPS / Year 1964 and the procedures in the Decree of the Chief of the National Police of the Republic of Indonesia No. 12 of 2010 and the advantages of the implementation of the death penalty in Indonesia the implementation process is carried out by shooting to death and has complete regulations in material and formal law, weaknesses in Indonesia there are clear regulations governing but not implemented in the application of the law. The state of Egypt, the death penalty is contained in the Criminal Code and other laws but in its implementation it is exclusive to the Criminal Procedure Code and Egypt has advantages over the procedural process where the imposition of the death penalty needs the approval of various parties until finally approved by the president, Egypt really implements the existing punishment, the weakness of the death penalty in Egypt lies in the implementation process which uses the method of hanging to death.